ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI PENCEMARAN LINGKUNGAN DI SMA NEGERI 4 PALEMBANG - Aseptianova Aseptianova; Sulton Nawawi; Lia Pesisa (Bioilmi: Jurnal Pendidikan, 2019)
This study aims to determine students' understanding of the concept of environmental pollution material in the school of SMAN 4 Palembang. This type of research is quantitative descriptive. The population of this study were all students of class XI MIPA SMAN 4 as many as 161 students. Sampling uses total sampling technique. Data collection techniques using test questions understanding concepts. The results of the study based on the analysis carried out using the percentage level of understanding of students 'concepts showed that students' understanding of concepts in environmental pollution material at Palembang State High School 4 was at high criteria with an average value of 65%. Conclusion the students' conceptual comprehension ability in environmental pollution material at Palembang State High School 4 with the highest value is found in the classifying indicator of 86% with very high criteria, and the lowest indicator is in the concluding indicator which is equal to 48% with the criteria being.